Outcome of the management of open ankle fractures in an ortho-plastic specialist centre. Issue 6 (June 2015) - Chummun, Shaheel; Wright, Thomas C.; Chapman, Thomas W.L.; Khan, Umraz
Abstract: Introduction: We reviewed the functional outcome of 68 patients with open ankle fractures managed in an orthoplastic specialist centre. Materials and methods: Patients managed at Frenchay Hospital over a 6 year period were divided into 3 groups: group P were patients initially seen and managed at Frenchay Hospital (an orthoplastic specialist centre), group S were patients stabilised at a different unit and referred for definitive management, while group R were patients managed in a different unit and referred following complications. Injuries were graded using the AO score and outcome was measured using the Enneking score (both validated). Results: 19 patients (group P, mean age: 43 years), 26 patients (group S, mean age: 41 years) and 23 patients (group R, mean age: 41.9 years) made the cohort. 82.4% patients required free tissue transfer. Mean AO scores of groups P, S and R were 11.5, 12.3 and 9.7 ( p  + 0.03). Mean number of procedures for P, S and R were 2.6, 3.5 and 4.2 ( p  = 0.0006). Mean follow up time was 55.5, 61.0 and 57.0 weeks respectively ( p  = 0.72). Mean Enneking scores for groups P, S and R were 63.3, 74.8 and 73.5 ( p  = 0.16). Conclusion: Patients from groups S and R underwent more procedures. However, a similar outcome can be achieved, highlighting the importance of managing such injuries in an orthoplastic specialist centre.